ABDULLA AVLONIY - Rahimjonova Xumora Ziyovuddin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In brief about Avloni, he has been creating for more than 30 years. He registered labor occasions of 1916 followed by revolutionary upheavals and national liberational problems.In the past , he said he had “left dozens of poems and school books, four theatre books”.When talking about his role in our history of our culture, we should emphasize two aspects : pedagogical activity and literary art. His pedagogical activity and ideas about education are really crucial source of defining the features of awareness which rose a new level in twentieth century. In the article we will observe such facilities as his pedagogical activity, hid educative behaviour, his call to science, his engagement the goodness and intelligence.